Serum vitamin D status and biochemical parameters of asthmatic children in Sokoto Metropolis, North-western Nigeria - Yeldu, Mohammed Haruna; Danjuma, Mohammed; Sulaiman, Mainasara Abdullahi; Muhammad, Jiya Nma; Illah, Garba Balkisu; Ibrahim, Yakubu; Shehu, Buhari (Asian Journal of Medical Sciences, 2019)
Background: Asthma is a common chronic disorder of the airways that is complex and characterized by variable and recurring symptoms. It is characterized by the occurrence of bronchial hyper responsiveness, airflow obstruction and an underlying inflammation. Several studies have proposed the association of vitamin D with increased incidence of asthma symptoms. Aims and Objectives: This study aimed at determining the serum vitamin D status and biochemical parameters among asthmatic children in Sokoto-Nigeria. Materials and Methods: The study population consisted of 120 subjects including 80 asthmatic children and 40 age-and sex-matched apparently healthy controls from two tertiary Hospitals in Sokoto Metropolis. Serum vitamin D, calcium, parathyroid hormone (PTH), immunoglobulin E (IgE) and magnesium were measured using standard techniques. Results: Mean serum vitamin D and magnesium were significantly (p ˂ 0.05) lower, while serum PTH and IgE were significantly higher (p˂0.001) in asthmatic children than in controls. Vitamin D insufficiency was found to be prevalent among the asthmatic children. There was no significant relationship between the low level of vitamin D and asthma severity. Conclusion: This study observed that, hypovitaminosis D and hypomagnesaemia occurred among asthmatic children, and asthma was more prone in the younger children than in their older counterpart. It is recommended that in order to avoid or limit the rate of children having asthmatic episodes, vitamin D and magnesium supplements should be used in the management of asthmatic children.